2020
DOI: 10.1177/1460408620921709
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of injuries and management of adolescent trauma in a combined adult and paediatric major trauma centre in United Kingdom

Abstract: Background Major trauma is a leading cause of death and disability in 16–18-year olds in the UK. Since the launch of major trauma centres (MTCs) in 2012 in UK, survival rates have improved on the whole. The aim of this study was to look at the pathways of 16–18-year olds through one MTC and patterns of rehabilitation provision. Material and methods A retrospective case notes review of all trauma patients aged between 16 and 18 years admitted to one MTC between October 2012 and May 2018. Results One hundred for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Furthermore, 92% of cases were discharged home and the median length of ICU stay was only 4 days. The overall good health outcomes can be attributed to (1) better-commissioned healthcare services for trauma-related injuries [11] such as trauma networks, air-ambulance services, specialist major trauma units, and RAAR services [19], and (2) a lower incidence of traumatic brain injuries, which are canonically associated with the worst health outcomes, compared to spinal and orthopedic injuries [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, 92% of cases were discharged home and the median length of ICU stay was only 4 days. The overall good health outcomes can be attributed to (1) better-commissioned healthcare services for trauma-related injuries [11] such as trauma networks, air-ambulance services, specialist major trauma units, and RAAR services [19], and (2) a lower incidence of traumatic brain injuries, which are canonically associated with the worst health outcomes, compared to spinal and orthopedic injuries [21].…”
Section: Discussionmentioning
confidence: 99%
“…Sports groups with the most head injuries were bicycle and ball sports. The relatively low prevalence and relatively better GOS is attributed to widespread awareness regarding traumatic brain injury in the population, better preventive measures in sports activity, such as restricting dangerous moves, tackles, better training of players use of appropriate headgear, and better healthcare services for immediate management of head injuries [19,21]. Still, there is a need to sustain the present practices and further improve the services such as encouraging headgear use in motor sports, contact and ball sports, and bicycle sports (as has been in practice for routine motorcycle use) [13,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scoping review also identified that some types of major trauma injury had more established and integrated pathways whilst others were underserved. [31][32][33][34][35][36][37][38]49,50 In summary, there is inherent inequity across major trauma care pathways that likely result in health inequality following major trauma, and which may be amplified by existing health and social inequalities. The NHS standard contract for major trauma care providers advocates for holistic trauma care that includes coordination of immediate and ongoing care, provision of information about major trauma care pathways, signposting to voluntary and/or non-government support services that can assist with psychological and social impacts of major trauma as well as supporting family members and carers during and after admission.…”
Section: Discussionmentioning
confidence: 99%
“…traumatic brain injury, spinal cord injury) than others (musculoskeletal injury). 35,37 Gaps were also noted in children's rehabilitation services 36 and in neurorehabilitation services for children under 4 years. 38 In addition, it was found that children presenting with injuries caused by suspected child abuse were less likely to trigger a major trauma alert, be taken to a major trauma centre and receive timely intervention despite having more serious injuries.…”
Section: Summaries Of Research Evidencementioning
confidence: 99%